Improving photo crosslink-ability and structural stability of amphibian-derived methacrylated collagen hydrogel - Tan, Lishan (Nanyang Technological University, 2024)
The escalating demand for sustainable biomedical materials has steered research towards the valorization of aquaculture waste. This project aims to solve the problem of underutilization of aquatic waste and market gap of photoresponsive collagen based hydrogel via the development of hydrogels derived from collagen of bullfrog skin for potential medical applications. The main aim is to develop biocompatible hydrogel with stable physicochemical properties to meet the market requirements in the biomedical field. To achieve this, a rigorous methodological approach was undertaken, which includes dual-modification of the extracted bullfrog collagen via methacrylation and diamine conjugation, as well as subsequent photocrosslinking to form the a stable hydrogel. The modification process was optimized through a series of experimental phases, assessing the dual modification potential and the sequential effects on the collagen matrix's physical and biological characteristics. Results from this project outlined a success in dual modification optimized for improved physical structural integrity as well as chemical and thermal stability under physiological conditions over 21 days, which could promote wound recovery when applied as dressing materials. The research ultimately proved that stable hydrogels from aquaculture waste collagen could be fabricated. Further research is recommended in refining the modification procedure and hydrogel precursor formulation such that cellular compatibility can be improved, and 3D printability of such hydrogels can be accessed.